Exploring LGBTQ Literature in Ecuador: Why it Matters - Freyn, Amy (Journal of University Teaching and Learning Practice, 2019)
This study explored what university students in Ecuador learned in a first ever LGBTQ Literature course, as well as if the course helped to build LGBTQ allies. The research explores not only the pedagogical strategies used in the development of and during the course, but also proposes a LBGTQ+ ally development teaching framework that can guide teachers in developing curricula around LGBTQ literature that will not only work against homophobia, heteronormativity, and heterosexism, but also provide teachers with an ultimate goal of developing LGBTQ allies in their schools. The results of the qualitative phenomenological research suggest that students not only learned by reading LGBTQ Literature, they also learned to become active, to use their voices, to embrace themselves and others, and to become stronger LGBTQ allies.